Dimethyltin dichloride-dibenzyl sulfoxide, a compound crystallizing with seven molecules in the asymmetric unit - Ng, S.W. (Chinese Journal Structural Chemistry, 2010)
Dimethyltin dichloride dibenzyl sulfoxide, ((CH(3))(2)SnCl(2)center dot O=S(CH(2)C(6)H(5))(2)), crystallizes in the orthorhombic space group P2(1)2(1)2(1) with a superstructure of. dimensions a = 11.9290(1), b = 19.50490(1), c = 55.7390(6) angstrom; Z = 28. The geometry of the five-coordinated tin atom in each of the seven independent adduct molecules is a square pyramid that is displaced towards a cis-trigonal bipyramid; the extent of displacement along the Berry pseudorotation pathway ranges from 20 to 45%.